Eco-Pedagogi Berbasis Religi Bagi Masyarakat Pesisir Tuban - M. Thoyyib; Mujib Ridlwan; Zakiyah Kholidah (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
This study aims to analyze the activities of religious-based Eco-Pedagogy for the Tuban Coastal community. This research is based on the stigma of the fishing community which is known to be slum and far from caring for the environment. Therefore, an education-based activity is needed that can change the character of the coastal community. The research was conducted on the coast of Jenu, Tuban, East Java for a period of six months from mid to late 2016. This study used qualitative research. Two stages were carried out during the research, namely knowing the level of religious understanding of coastal communities, especially related to environmental preservation texts and internalizing the values ​​of revelation texts through a religious approach. The results show that the coastal community of Tuban is known as a religious community, but on the one hand it is also known as slums. Religion is the basis for them in educating the behavior of caring for the environment. Several things have been done in religious-based eco-pedagogy for the coastal community of Tuban, including: understanding the community towards the verses of the Qur'an which contain concern for the environment, raising public awareness of loving the environment, building stakeholder involvement so that they are together to care for the environment.